2020
DOI: 10.1101/2020.10.11.20210864
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Awareness, Perception and Practice of COVID 19 Prevention among Residents of a State in the South-South Region of Nigeria: Implications for Public Health Control Efforts

Abstract: Background This research explored awareness, perception, and practice of COVID 19 prevention among residents of communities in all the local government areas (districts) in Rivers State during the early stages of the pandemic response. Design This was a descriptive cross-sectional survey which employed an interviewer-administered four-page questionnaire built into the Open Data Kit application for android phones. Knowledge and practice scores were computed by scoring every correct response/action as 1 and wro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 10 publications
(15 reference statements)
2
9
1
Order By: Relevance
“…Television and radio, which are effective channels for disseminating health information as they can reach larger percentage of people within a country, were the major sources of information in this study. This agrees with previous reports across the country [8,11,18]. Traditional means of information dissemination however, were not popular, possibly as a result of the high proportion of well-educated people among the respondents, while the lockdown and social distancing measures imposed by the Government might also have played a role [19].…”
Section: Consideringsupporting
confidence: 90%
See 2 more Smart Citations
“…Television and radio, which are effective channels for disseminating health information as they can reach larger percentage of people within a country, were the major sources of information in this study. This agrees with previous reports across the country [8,11,18]. Traditional means of information dissemination however, were not popular, possibly as a result of the high proportion of well-educated people among the respondents, while the lockdown and social distancing measures imposed by the Government might also have played a role [19].…”
Section: Consideringsupporting
confidence: 90%
“…In this study, 59% of participants reported washing their hands with water and soap. This figure is lower than 92.7% reported in an online survey with a higher sample size in Saudi Arabia, 81.6% in Enugu and 90.5% recorded in the wide spread community survey in Rivers State, where surprisingly, only 39% of participants demonstrated all handwashing steps satisfactorily [2,18]. The steps of hand washing were however, not explored in this series.…”
Section: Consideringcontrasting
confidence: 72%
See 1 more Smart Citation
“…For example, in a study in Nigeria, only 39% of respondents washed all critical parts of their hands correctly when asked to demonstrate handwashing, compared to 90.5% of respondents who reported practicing regular handwashing with soap and water to prevent COVID-19. 38 We tried to reduce reporting bias and capture detailed experiences by including several open-ended questions and asking for follow-up explanations to closed-ended questions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study in Nigeria, only 39% of respondents washed all critical parts of their hands correctly when asked to demonstrate handwashing, compared to 90.5% of respondents who reported practicing regular handwashing with soap and water to prevent COVID-19. 38 We tried to reduce reporting bias and capture detailed experiences by including several open-ended questions and asking for follow-up explanations to closed-ended questions. Finally, we targeted respondents who resided in villages that had completed the MANTRA program that installed village-level piped water and created high levels of sanitation access, 30 and therefore results related to WASH practices may not be generalizable to other villages with lower levels of water and sanitation access.…”
Section: Discussionmentioning
confidence: 99%